Impact of stock market liquidity and external factors on herding behavior in the Amman Stock Exchange - Raneem Ghazi Aldeki (Journal of Enterprise and Development (JED), 2024)
Purpose — The research investigation was centered on the potential for herding behavior in the Amman Stock Exchange. The major goal of the current investigation is to identify any herding behavior that may occur, including behavior caused by liquidity and global factor drivers (such as oil prices and Fed fund rates).Method — The study employed the quantitative research method. The sample consists of 50 observations from 171 companies, and the data were collected from monthly records spanning January 2019 to March 2023. The Generalized Method of Moments (GMM) and a deductive approach were utilized in the quantitative methodology of this study.Result — At this stage, employing a CSSD regression analysis makes it possible to observe evidence of herding behavior in the left tail. The study also found no evidence suggesting that stock market liquidity affects herding behavior in the right tail during periods of both high and low liquidity. However, it did find evidence indicating that liquidity affects herding behavior in the left tail. The Amman capital market has demonstrated that herding behavior is not significantly influenced by global factors.Practical implications  — This study suggests that the Amman Stock Exchange should make information accessible to all investors to encourage them to take an active role in making their own investment decisions.